Adsorptive characteristics of isoniazid on powdered activated carbon: - Dispersion interactions at the solid-solution interface - ÇALIŞKAN SALİHİ, ELİF; AYDIN, ESRA (TAYLOR & FRANCIS INC, 2017)
The presence of antibiotic residues in the aquatic environment poses a potential risk to living organisms due to the development of antibiotic resistance in bacteria. In the present study, the removal of isoniazid by commercial powdered activated carbon was studied in aqueous solutions. The adsorption experiments were done as a function of time, concentration, temperature, and pH in order to understand the adsorption mechanism. The Langmuir and the Freundlich isotherms were used to model the equilibrium data. The results showed that isoniazid was physisorbed on the surface of the activated carbon by - dispersion interactions.
Keywords: Adsorption; activated carbon; antibiotics; dispersion interactions; PERSONAL CARE PRODUCTS; SPENT BLEACHING EARTH; AQUEOUS-SOLUTION; AQUATIC ENVIRONMENT; WASTE-WATER; HUMAN PHARMACEUTICALS; SURFACE-CHEMISTRY; DRINKING-WATER; REMOVAL; ACID